Hydrodynamic Modeling for Enhance Water System in Katingan Tidal Lowlands - Kamil, Insanul; Rachmad Jayadi; Adam Pamudji Rahardjo; Yakubson (Fakultas Teknik, Universitas Brawijaya, 2024)
A study was conducted on the Katingan tidal lowland area with hydro-topography A and B. The lowland area has good irrigation capability but low drainage capability, resulting in excessive inundation. This study aims to enhance drainage capability and control water levels in rice fields. HEC-RAS is used to model the hydrodynamics of canals and rice fields. There are three scenarios for improving the water system, namely embankments (1), embankments and pipes (2), and embankments, pipes, and gates (3). In the normalized canals, inundation in the middle of the rice field is more than 35 cm and continuous inundation. This is due to the low elevation of the middle area, which results in low drainage capability. The embankment (1) prevents the tide from overflowing into the rice fields, but the rice fields are deficient in water. Embankments and pipes (2) can fulfill the water need for irrigation but not increase drainage capability. Embankments, pipes, and gates (3) can maintain irrigation capability and improve drainage capability. The water level can be maintained at 7-10 cm at land elevation +3.40 m, but land with elevation +3.50 m has a water deficiency. The third scenario is the most appropriate for controlling water levels in rice fields. Water system improvement in tidal lowlands must be considered to avoid water deficiency. Drought in tidal lowlands causes pyrite to oxidize, leading to increased soil acidity. Therefore, irrigation capability must be maintained to improve the water system on land with hydro-topography A and B.